EFL College Student’s Perception in Using Movie Animations from Little Fox Youtube Channel as Autonomous Learning Activities - Zahra, Nadafa Namira; Marlina, Leni (Journal of English Language Teaching, 2024)
The aim of this research is to reveal students' perceptions of the use of movie animations from the "Little Fox" YouTube channel as an autonomous learning activity. This research uses descriptive research with a quantitative approach. The population of this study was the Advanced Listening class at Faculty of Language and Arts, Universitas Negeri Padang with a sample of the K5 Advanced Listening class (Prodi K5 English, Language Education Program). This research used a total sampling technique because the class where learning using visual media was implemented was only the K5 Advanced Listening class. The research instruments used to collect the data were  a questionnaire with 30 closed statements using 4 Likert scales, and an interview with 5 main questions about students’ perception in using movie animations from “Little Fox” YouTube Channel as autonomous learning activities. The results of this research are from a physical aspect and a psychological aspect. Firstly, from the physical aspect the results showed that the majority of students liked and felt involved in watching animated videos from the YouTube channel "Little Fox," with positive perceptions of their impact on comprehension, visual and auditory senses, and enjoyment in learning English. The total average of perception indicators in the physical aspect is 3.03 (Positive).  Secondly, from the psychological aspect the results showed that the use of animated videos from the YouTube channel "Little Fox" significantly increased students' interest, self-confidence and engagement in English learning, reflecting the positive psychological impact of the channel's content.  The total average of perception indicators in the psychological aspect is 3.05 (Positive). Since the students' perceptions on both physical and psychological aspects are Positive, the other classes are suggested to use the Little Fox YouTube channel in a similar way as an autonomous learning activity.